2018
DOI: 10.1007/s00248-017-1139-z
|View full text |Cite
|
Sign up to set email alerts
|

Azospirillum brasilense Increases CO2 Fixation on Microalgae Scenedesmus obliquus, Chlorella vulgaris, and Chlamydomonas reinhardtii Cultured on High CO2 Concentrations

Abstract: Mutualism interactions of microalgae with other microorganisms are widely used in several biotechnological processes since symbiotic interaction improves biotechnological capabilities of the microorganisms involved. The interaction of the bacterium Azospirillum brasilense was assessed with three microalgae genus, Scenedesmus, Chlorella, and Chlamydomonas, during CO fixation under high CO concentrations. The results in this study have demonstrated that A. brasilense maintained a mutualistic interaction with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 40 publications
0
28
0
Order By: Relevance
“…The use of mixed cultures to promote algae growth through mutualistic interaction is an emerging research frontier in algal biotechnology [17]. Emulating natural symbioses, engineers can design processes that utilize mutually beneficial organisms with biotechnological applications.…”
Section: Introductionmentioning
confidence: 99%
“…The use of mixed cultures to promote algae growth through mutualistic interaction is an emerging research frontier in algal biotechnology [17]. Emulating natural symbioses, engineers can design processes that utilize mutually beneficial organisms with biotechnological applications.…”
Section: Introductionmentioning
confidence: 99%
“…Nutritional conditions seem to modulate the interaction between these two microorganisms; in experiments when the interaction was supported by a nutrient-rich medium, production of both the signal molecules IAA and tryptophan was detected but not when this interaction began with nitrogen-free (N-free) or carbon-free (C-free) media [62]. The exchange of IAA and tryptophan between A. brasilense and the microalgae Chlorella vulgaris, Scenedesmus obliquus, and C. reinhardtii was corroborated by Choix et al [63] in experiments under different concentrations (15%, 25%, and 35%) of CO 2 . In all concentrations, the bacterium and the microalga, respectively, produced AIA and tryptophan during all the experimental time, indicating that the synthesis of this compound is not affected by high CO 2 concentrations.…”
Section: Mechanisms Acting In Mutualistic Co-culturesmentioning
confidence: 78%
“…For instance, the cultivation of A. brasilense with the microalgae S. obliquus, C. vulgaris, and C. reinhardtii under high CO 2 concentrations, as discussed earlier, significantly enhanced microalgal growth as well as metabolite accumulation on each microalga. The authors reported an increase of carbohydrates, proteins, and lipids under all gas mixtures evaluated [63]. Higher levels of microalgal carbohydrates have also been reported as a result of co-cultivation with bacteria.…”
Section: Enhancement Of Biomass and Metabolite Productionmentioning
confidence: 79%
See 1 more Smart Citation
“…and Scenedesmus sp. have attracted considerable attention recently, diverse macro-algae, commonly referred to as seaweed, can also be a useful industrial resource due to their continuously growing productivity, the increasing demand for seafood and their well-established mass cultivation and harvesting technologies in the nonarable coastal ocean over the past hundred years (Chennubhotla et al 1987;Buchholz et al 2012;Leupold et al 2013;Angus 2017;Buschmann et al 2017;Choix et al 2018).…”
Section: Introductionmentioning
confidence: 99%